2014
DOI: 10.4236/eng.2014.63016
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Method Applied to the Eigenvalue Analysis of Flexible Rotors Supported by Journal Bearings

Abstract: This work deals with a finite element procedure developed to perform the eigenvalue analysis of damped gyroscopic systems, represented by flexible rotors supported on fluid film journal bearings. The rotor finite element model is based on the Timoshenko beam theory, accounting for the shaft rotary inertia and gyroscopic moments. The governing equations for the hydrodynamic journal bearing are obtained through the Galerkin weighted residual method applied to the classical Reynolds equation. A perturbation schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…He observed that low imbalance in the system provides higher stability for the system. Miranda and Faria [5] have worked on flexible journal bearings based on Fluid structural interaction along with finite element analysis to find the actual behavior of the systems. Fluid film damping effect is also simulated.…”
Section: ©Ijraset: All Rights Are Reservedmentioning
confidence: 99%
“…He observed that low imbalance in the system provides higher stability for the system. Miranda and Faria [5] have worked on flexible journal bearings based on Fluid structural interaction along with finite element analysis to find the actual behavior of the systems. Fluid film damping effect is also simulated.…”
Section: ©Ijraset: All Rights Are Reservedmentioning
confidence: 99%